QARINAH AS EVIDENCE IN DECIDING CASE - Umar, Mukhsin Nyak (UIN Ar-Raniry, 2015)
Qarinah as evidence leading to a conviction has been used by judges as the consideration basis in resolving a case. Its uses as evidence is still controversial especially in Fiqh. This is not the case in positive law as positive laws are regulated by a nation. The most important part of qarinah as evidence is how the results of technological advancements such as DNA could be used as qarinah. Positive law seems to have adopted DNA as qarinah so as to use it in imposing a legal decision. In reference to the Islamic law, can a DNA technology be used as qarinah? Apparently further research regarding this topic is required. This article discusses fundamental arguments for possible adoption of DNA as qarinah evidence.